The impact of masticatory ability as evaluated by salivary flow rates on obesity in japanese: The Toon health study. (9th May 2015) - Maruyama, Koutatsu; Nishioka, Shinji; Miyoshi, Noriko; Higuchi, Kana; Mori, Hiromi; Tanno, Sakurako; Tomooka, Kiyohide; Eguchi, Eri; Furukawa, Shinya; Saito, Isao; Sakurai, Susumu; Nishida, Wataru; et al.
<x xml:space="preserve">Abstract</x> Objective This study examined the associations of masticatory ability evaluated by chewing‐gum‐stimulated salivary flow rate with anthropometric indices among a general Japanese population. Methods In total, 921 Japanese men and women aged 30–79 years participated in this cross‐sectional study. Saliva production was stimulated by 5 min of gum chewing, then collected; salivary flow rate was calculated as g/min. Overweight, abdominal obesity in terms of waist circumference (WC), and waist–hip ratio (WHR), and elevated skinfold thickness statuses were determined. Results The multivariable odds ratio and 95% confidence intervals of overweight, abdominal obesity (WC, WHR), and elevated skinfold thickness status for highest vs. lowest quartile of salivary flow rate were 0.59 (0.37‐0.95, P for trend = 0.02), 0.65 (0.43‐0.98, P = 0.03), 0.54 (0.35‐0.83, P < 0.01), and 0.61 (0.39‐0.96, P < 0.01), respectively. The linear trends of multivariable‐adjusted means of BMI, WC, WHR, and skinfold thickness according to quartiles of salivary flow rate did not vary after stratification by overweight status. Conclusions Higher stimulated salivary flow rate, a surrogate marker for mastication ability, was associated with lower prevalence of overweight, abdominal obesity (whether WC‐ or WHR‐defined), and elevated skinfold thickness among the general Japanese population.